Analysis of the Impact of Knowledge on Sustainable Travel Choices: an Empirical Study with Informational Videos and Gamified Quizzes - Murad, Syed; Law, Effie Lai-Chong (Interacting with computers, 2025)
Abstract Carbon emissions from transport are increasing on a global scale with transport accounting for the largest portion. While there is greater awareness of climate change, few people are willing to change their travel habits. To gain a better understanding of this phenomenon, we were motivated to conduct a study to identify the obstacles encountered by travellers when opting for sustainable transport modes, assess their knowledge of carbon emissions from various transport modes and explore how this knowledge affects their decision-making process. The study employed mixed-method approaches, including the use of informational videos and gamified quizzes for intervention, pre- and post-intervention knowledge assessment tests, semi-structured interviews, observations, Self-Assessment Manikin for emotion measures and card sorting. The findings primarily derived from thematic analysis indicated that knowledge-based intervention can be a strong catalyst to encourage sustainable attitude and behaviour change. Insights so gained have important theoretical and practical implications for designing sustainable behaviour change in the future, especially the deployment of persuasive technology.